2018
DOI: 10.1021/acs.energyfuels.7b03175
|View full text |Cite
|
Sign up to set email alerts
|

Slow Pyrolysis Performance and Energy Balance of Corn Stover in Continuous Pyrolysis-Based Poly-Generation Systems

Abstract: In order to analyze pyrolysis performance and energy balance of corn stover pyrolysis, a poly-generation pyrolysis unit that coproduced biochar, pyrolysis gas, and liquids was used. Corn stover was naturally dried and crushed to lengths of 4–7 mm before pyrolysis at 450, 550, and 650 °C. The physical and chemical properties, yield rate, and influence of technological parameters were analyzed. In addition, a full energy balance analysis was carried out. The results show that the quality of corn stover char was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Continuous pyrolysis conditions include pyrolysis temperature, material residence time, and feeding rate. The heating rate is another important factor that is affected by the above factors, and as such cannot be controlled independently from the other parameters (Cong et al, 2018;. Slow pyrolysis has a wide range of working conditions using moderate temperatures (up to 600 °C) to produce biochar (Basu, 2010;Cong et al, 2017).…”
Section: Setting Of Process Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous pyrolysis conditions include pyrolysis temperature, material residence time, and feeding rate. The heating rate is another important factor that is affected by the above factors, and as such cannot be controlled independently from the other parameters (Cong et al, 2018;. Slow pyrolysis has a wide range of working conditions using moderate temperatures (up to 600 °C) to produce biochar (Basu, 2010;Cong et al, 2017).…”
Section: Setting Of Process Parametersmentioning
confidence: 99%
“…The mass distribution of different fractions produced by slow pyrolysis typically changes depending on residence time, particle size, and pyrolysis temperature. In order to remove any variability associated with the residence time and particle size, the mean residence time was pre-set as 30 min based on preliminary tests and previous studies (Cong et al, 2018) and the particles of comparable size were used, as introduced in Section 2.1.…”
Section: Mass Distribution Of Pyrolysis Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, from a techno-economic perspective, it is suggested that this kind of BIPP system with biochar returned to soil and biofuels used for direct energy use, power generation, and industrial use should be developed on a relatively large scale with higher pyrolysis temperatures between 550 and 650 °C. There also are studies showing that the variation of pyrolysis parameters could influence the profitability of the process technology 35 , 36 . To date, there has been a large number of published studies discussing properties of biochar and biofuels produced at pyrolysis temperatures of 300–700 °C 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Charcoal exhibited a more intense rate of weight loss during the second stage, and this occurred at a distinctly lower temperature than that of the semi-coke. The curve of biotar was the most tortuous, which indicated that the weight loss fluctuated throughout the process owing to its complex components consisting of phenols, amides, and lipids with >20C atoms [31]. The burnout indices and integrated combustion indices of the materials are listed in Table . 2.…”
Section: Tablementioning
confidence: 99%